Epitope Mapping of the Anti-Urokinase Monoclonal Antibody 5B4 by Isolated Domains of Urokinase - Corti, Angelo; Sarubbi, Edoardo; Soffientini, Adolfo; Nolli, M Luisa; Zanni, Arturo; Galimberti, Marina; Parenti, Franco; Cassani, Giovanni (Thrombosis and Haemostasis, 1989)
The amino terminal fragment (ATF) of urokinase-type plasminogen activator (uPA) is a degradation product comprising the entire growth factor-like and kringle domains. It has been previously shown that ATF is able to bind to the u-PA receptor through the growth factor-like domain and that the anti u-PA monoclonal antibody 5B4 (Mab 5B4) binds to ATF preventing u-PA receptor binding. To localize more precisely the epitope recognized by Mab 5B4, ATF was subfragmented by controlled enzymatic proteolysis with V8 protease.Three subfragments of 4,000 Mr (F-4k), 11,000 Mr (F-llk) and 12,0 Mr (F-12k) were purified from the reaction mixture and characterized. SDS-PAGE under reducing and non-reducing conditions, N-terminal aminoacid sequence analysis and C-terminal aminoacid analysis of each fragment indicate that F-4k and F-llk correspond to intact growth factor-like domain and kringle domain (residues 4-43 and 44-135 respectively) while F-12k corresponds to the kringle. domain cleaved in the first loop at the glu52-gly53 bond.By Western blot and competitive binding experiments we show that Mab 5B4 recognizes an epitope located on the kringle domain of u-PA and that the binding is strongly reduced when the kringle contains an additional cleavage in its first loop.Since the receptor binding site of u-PA has been previously shown to be located on the growth factor-like domain, Mab 5B4 inhibits the binding of uPA to its cellular receptor likely by steric hindrance.Besides the proven utility in epitope localization of anti u-PA monoclonal antibodies, these u-PA fragments may represent powerful tools for studies of structure-function relationship of u-PA.
Keywords: Urokinase-type Plasminogen Activator; Kringle; Growth factor-like domain; Monoclonal antibody; V8 protease